Expression of non-phosphorylatable S5A-L-plastin exerts phenotypes distinct from L-plastin deficiency during podosome formation and phagocytosis - Lin, Xue; Krishnamoorthy, Praveen; Walker, Emma C.; Joshi, Hemant; Morley, Sharon Celeste (Frontiers in Cell and Developmental Biology, 2023)
Introduction: The actin cytoskeleton remodels to enable diverse processes essential to immunity, such as cell adhesion, migration and phagocytosis. A panoply of actin-binding proteins regulate these rapid rearrangements to induce actin-based shape changes and to generate force. L-plastin (LPL) is a leukocyte-specific, actin-bundling protein that is regulated in part by phosphorylation of the Ser-5 residue. LPL deficiency in macrophages impairs motility, but not phagocytosis; we recently found that expression of LPL in which the S5 residue is converted to a non-phosphorylatable alanine (S5A-LPL) resulted in diminished phagocytosis, but unimpaired motility. Methods: To provide mechanistic insight into these findings, we now compare the formation of podosomes (an adhesive structure) and phagosomes in alveolar macrophages derived from wild-type (WT), LPL-deficient, or S5A-LPL mice. Both podosomes and phagosomes require rapid remodeling of actin, and both are force-transmitting. Actin rearrangement, force generation, and signaling rely upon recruitment of many actin-binding proteins, including the adaptor protein vinculin and the integrin-associated kinase Pyk2. Prior work suggested that vinculin localization to podosomes was independent of LPL, while Pyk2 was displaced by LPL deficiency. We therefore chose to compare vinculin and Pyk2 co-localization with F-actin at sites of adhesion of phagocytosis in AMs derived from WT, S5A-LPL or LPL−/− mice, using Airyscan confocal microscopy. Results: As described previously, podosome stability was significantly disrupted by LPL deficiency. In contrast, LPL was dispensable for phagocytosis and was not recruited to phagosomes. Recruitment of vinculin to sites of phagocytosis was significantly enhanced in cells lacking LPL. Expression of S5A-LPL impeded phagocytosis, with reduced appearance of ingested bacteria-vinculin aggregates. Discussion: Our systematic analysis of the regulation of LPL during podosome vs. phagosome formation illuminates essential remodeling of actin during key immune processes.